Batang Toru Rivers Water Quality Analysis of Batangtoru River in South Tapanuli District, North Sumatra Province - Rasyid, Fahmi; Nasution, Zulkifli; Wahyungsih, Hesti (Journal of Environmental and Development Studies, 2024)
Water is a natural resource whose quality needs to be maintained. In order to protect against pollution or achieve good river water quality, it is necessary to make good water management efforts to maintain water functions in accordance with water quality standards. The purpose of this research is to analyze the water quality of the Batangtoru River and the factors that affect the water quality of the Batangtoru River. This research was conducted in the river located in South Tapanuli Regency, North Sumatra Province, Indonesia, for two months in November and December 2020 with test parameters Total Suspended Solid (TSS), Biological parameters in the form of Biological Dissolved Oxygen (BOD), E.Colli, and chemical parameters in the form of Copper (Cu), Zinc (Zn), Cadmium (Cd), Nitrite (NO2-N), and Ammonia (NH3- N). The research results showed that the water quality of the Batangtoru river was: TSS 50 mg/L, BOD 3 mg/L, Cu 0.02 mg/L, Zn 0.05 mg/L, Cd 0.01 mg/L, NO2-N 0.06 mg/L, NH3-N and E. Colli 0 mg/L. These results based on PP 82 of 2001 show that the test parameter values have exceeded water quality standards. And it is included in class II, which means that the quality of the Batangtoru River is experiencing light pollution. Â